Behavioral Activation for Treatment-resistant Depression: Theoretical Model and Intervention Protocol (BA-TRD) - Michel A. Reyes-Ortega; Jorge Barraca; Jessica Zapata-Téllez; Alejandra M. Castellanos-Espinosa; Joanna Jiménez-Pavón (Clínica y Salud. Investigación Empírica en Psicología)

(untitled)
Background: Treatment-resistant depression (TRD) is a severe public health problem and a condition uncommonly addressed by psychological therapies. This paper presents a theoretical model, grounded in established learning principles and in the perspective of behavioral activation (BA), to explain its constitution and development. Method: A review of theoretical models and empirical research on TRD was conducted in major databases. Results: The model reflects how patients with TRD are more susceptible to becoming trapped in their condition by seeking to avoid discomfort through avoidance and escape behaviors, which increasingly drives them away from sources of positive reinforcement. Based on this model, a BA-based intervention protocol is suggested for the treatment of TRD. Through six phases (in a total of thirteen sessions), the protocol guides the intervention towards the reestablishment of personalized routines to increase the probability of reinforcement and reduce avoidance behaviors. Conclusions: Although the model holds significant potential to become an effective intervention in TRD, future research will allow the evaluation of the efficacy of the protocol as a standalone intervention.